2013
DOI: 10.1089/chi.2012.0119
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Providers' Self-Efficacy and Outcome Expectations for Childhood Obesity Counseling

Abstract: Background: Primary care providers have a role in the prevention and management of childhood obesity. We explored the relationship of providers' self-efficacy, outcome expectations, and practice level support with childhood obesity counseling frequency.Methods: Providers (n = 123) completed a survey that assessed their self-efficacy, outcome expectations, and reported obesity counseling frequency. A practice level assessment tool was used to characterize the practices. We analyzed data using frequencies and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Insufficient confidence has been quoted as a barrier both to delivering weight loss counselling and to raising the issue of weight with patients initially [ 23 25 ]. Studies have shown associations between both high self-efficacy and high outcome expectation in this area and the amount of counselling performed by the doctor [ 26 , 27 ]. A systematic review in 2011 found that health professionals felt underprepared and lacking sufficient knowledge to deal with obesity and that they considered current approaches to treatment to be ineffective [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insufficient confidence has been quoted as a barrier both to delivering weight loss counselling and to raising the issue of weight with patients initially [ 23 25 ]. Studies have shown associations between both high self-efficacy and high outcome expectation in this area and the amount of counselling performed by the doctor [ 26 , 27 ]. A systematic review in 2011 found that health professionals felt underprepared and lacking sufficient knowledge to deal with obesity and that they considered current approaches to treatment to be ineffective [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond logistical and cost barriers associated with conducting obesity interventions in primary care settings, primary care providers in the USA, Canada, Europe, Australia, and elsewhere have described barriers related to primary care provider training, knowledge and skills, and attitudes about obesity prevention and treatment [17–26]. While recent studies suggest increased provider comfort in screening and counseling for obesity [27, 28], rates of obesity prevention and treatment activities in primary care remain low in many countries, including the USA Israel, Australia, and several European countries [25, 29, 30•, 3134]. Furthermore, primary care providers have expressed reservations about the effectiveness of provider-delivered obesity prevention and treatment strategies, citing concerns regarding the obesogenic environment, lack of parent motivation to make weight-related behavioral changes for themselves and their family, and low parent concern about child weight [16, 20, 22, 24, 27, 32, 3436].…”
Section: Introductionmentioning
confidence: 99%
“… 14 For those who recognize that a child is overweight, studies suggest that some providers may believe that there is little that can be done in primary care to improve the child’s weight status. 15 , 16 Alternatively, the provider previously may have addressed weight management with the family. Lack of incentives or financial reimbursement also could play a role—notably, the benchmarks with the highest rates of performance were the HEDIS measures that are used by health insurance companies to determine quality and billing.…”
Section: Discussionmentioning
confidence: 99%